An investigation of the highly conserved long non-coding RNA CEROX1 - Roberts, K (2018)
Amid growing catalogues of long non-coding RNAs (lncRNAs), experimentally characterised examples are few, especially for the recently identified subpopulation that are enriched in the cytoplasm. Amongst these are lncRNAs whose activity is proposed to be mediated by the competitive endogenous RNA (ceRNA) mechanism. De-repression of miRNA targets results in concerted gene expression changes following ceRNA modulation in numerous in vitro models, but evidence of in vivo physiological relevance is lacking.